2014
DOI: 10.15407/ujpe59.04.0379
|View full text |Cite
|
Sign up to set email alerts
|

Smoky Plasma in a Dust Flame

Abstract: The results of experimental investigation of the influence of 0.1÷5.0 mass percent of K2CO3 and KCl additives on the dispersion of combustion products, which were obtained by the combustion of an Al gas suspension in a laminar diffusion flame, are presented. The extreme dependence between the average particle size of Al2O3 and the additive concentration () was experimentally observed. At the K2CO3 additive concentration over 0.5%, the increase in the average particle size of Al2O3 (10 ∼ 50 nm for = 5%) was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Reducing the size of Al 2 O 3 nanoparticles with increasing concentration of impurities was confi rmed experimentally [10,15]. It has been found that the dependency of the average particle size Al 2 O 3 on the concentration of easily ionized additive has an extremum (a minimum, Fig.…”
Section: Specifi Cities Of the Ionized Aerosol Coagulationmentioning
confidence: 84%
See 3 more Smart Citations
“…Reducing the size of Al 2 O 3 nanoparticles with increasing concentration of impurities was confi rmed experimentally [10,15]. It has been found that the dependency of the average particle size Al 2 O 3 on the concentration of easily ionized additive has an extremum (a minimum, Fig.…”
Section: Specifi Cities Of the Ionized Aerosol Coagulationmentioning
confidence: 84%
“…Thermal ionization of the additives leads to a redistribution of charges between the condensed and gas phases, a change in the charge of the particles and, hence, a change in the rate of their coagulation [7,10,15].…”
Section: Specifi Cities Of the Ionized Aerosol Coagulationmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray phase and energy-dispersive analyses and electron microscopy of combustion products [9,34,39] showed that, unlike nanoparticles of aluminum, iron, and titan oxides, whose particles are solid spheres, zinc and magnesium oxides are formed in the form of hexagonal (ZnO, Fig. 3a) and cubical (MgO; Fig.…”
Section: Production and Properties Of Dust Flames Of Gas Suspensions mentioning
confidence: 99%